(untitled) (Olhar de Professor, 2022)
This text is an excerpt of a master’s research, we discuss the influence network of actors in the business movement that has strengthened in recent years, more specifically, dealing with the actors that make up the Movement for the Base. The objective is to present the programs offered to state public education networks in the Southeast with objectives aimed at the Base’s policy and that have some type of interference, support or funding from the private actors that are part of the Movement. The procedures used in this qualitative research were targeted searches on the websites of the southeastern state education secretariats, between the years 2013 to 2019. The results indicate a predilection of private actors to act in teacher training, in an era called by Ball and Olmedo (2013) from the era of philanthrocapitalists, who build their investments and offer consultancy and programs in search of potential profits.